2009
DOI: 10.1109/tmi.2008.2008954
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Optical Tracking of Flexible Laparoscopic Ultrasound: Model-Based Online Detection and Correction of Magnetic Tracking Errors

Abstract: Abstract-Electromagnetic tracking is currently one of the most promising means of localizing flexible endoscopic instruments such as flexible laparoscopic ultrasound transducers. However, electromagnetic tracking is also susceptible to interference from ferromagnetic material, which distorts the magnetic field and leads to tracking errors. This paper presents new methods for real-time online detection and reduction of dynamic electromagnetic tracking errors when localizing a flexible laparoscopic ultrasound tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…One of the earlier attempts to compensating dynamic errors intraoperatively involved focusing on the region of interest alone to apply the distortion model Nakamoto et al, 2008). A more recent approach to detect and reduce dynamic EM tracking errors intraoperatively makes use of a tracking redundancy and a model based approach instead of a pre-computed distortion function (Feuerstein et al, 2009). …”
Section: Challenges -Em Tracking Accuracymentioning
confidence: 99%
“…One of the earlier attempts to compensating dynamic errors intraoperatively involved focusing on the region of interest alone to apply the distortion model Nakamoto et al, 2008). A more recent approach to detect and reduce dynamic EM tracking errors intraoperatively makes use of a tracking redundancy and a model based approach instead of a pre-computed distortion function (Feuerstein et al, 2009). …”
Section: Challenges -Em Tracking Accuracymentioning
confidence: 99%
“…Although Cheung et al 7 reported an AR system based on EM tracking, the investigators do not describe where the sensors were placed on the two imaging probes, what the EM tracking errors associated with these locations were, or whether or not these locations were clinically practical. Feuerstein et al 20 proposed a hybrid optical-EM method to track the flexible tip of the LUS probe. However, the study focused on tracking the LUS probe only and not the laparoscope, and the attachment of the sensor appears to be a laboratory solution (i.e., cannot be implemented clinically).…”
Section: Introductionmentioning
confidence: 99%
“…To address airway deformation, Gergel et al applied particle filtering to all camera positions and orientations acquired by EMT and projected them to a previously segmented centerline of the bronchial tree [4], so they assume a bronchoscope camera that is always moving along the centerline of the airways; however this is a hard constraint since it is easily violated by a bronchoscopist in the operating room. Otherwise, the measurement inaccuracies of EMT are difficult to correct, unless combined with optical tracking [5,6]. Furthermore, a combination of image-and sensor-based methods for bronchoscope tracking was originally proposed by Mori et al [7].…”
Section: Introductionmentioning
confidence: 99%